Advanced Light Management for Encapsulated Silicon Solar Cells: An Antireflective Textured Film with a Down-Shifting Lead-free Perovskite Cs2AgxNa1-xBiyIn1-yCl6 Phosphor - Kong, Mengqin; Raievska, Oleksandra; Stroyuk, Oleksandr; Barabash, Anastasia; Wu, Zhenni; Tian, Jingjing; Erban, Christof; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Light management (LM) is the key to the encapsulation of high-performance silicon (Si) photovoltaic devices (PVs). In this work, simulation analyses provide meaningful insights into optical losses and guide the improvement of the PV performance of the encapsulated silicon solar cells (Encap-Si SCs). An antireflective layer, textured polydimethylsiloxane (PDMS), is designed to reduce reflection losses, especially at a lower illumination intensity, thereby achieving an improvement of 10.89% in the short-current density (JSC) and hence 12.67% in the power conversion efficiency (PCE) when illuminated at an incident angle of 60°. Subsequently, a luminescence down-shifting material, lead-free Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) double perovskite phosphor, is incorporated into the PDMS film to further enhance the energy yield in the ultraviolet (UV) region. The textured PDMS film with an optimized CANBIC content ultimately achieves a significant improvement in PCE from 21.770 to 23.136%. This enhancement is attributed to the increase in JSC by 2.381 mA/cm2 due to the reduced reflection losses (by antireflective PDMS) and down-converted UV energy (by CANBIC), providing a remarkable advance in LM toward highly efficient encapsulated PVs.
CRIS-Team Scopus Importer:2024-08-23
Keywords: antireflective layer; down-shifting layer; encapsulated Si solar cell; lead-free perovskite phosphor; optical simulation

Closing the loop: recycling of MAPbI3 perovskite solar cells - Wu, Zhenni; Sytnyk, Mykhailo; Zhang, Jiyun; Babayeva, Gülüsüm; Kupfer, Christian; Hu, Jin; Arnold, Simon; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Energy and Environmental Science, 2024)
Closed-loop recycling is crucial in the rapidly expanding era of photovoltaic deployment. Yet, the recycling of commercial silicon photovoltaic modules presents challenges due to laborious component separation. In contrast, layers in solution-processed solar cells can be separated with relative ease through selective dissolution. In this study, we report on the recovery of every layer in a planar MAPbI3 perovskite solar cell using a layer-by-layer solvent extraction approach, followed by purification or modification to restore quality. This method potentially allows for up to 99.97% recycled mass, thereby conserving resources and reducing waste. We assessed material quality by substituting each fresh material with its recycled equivalent during solar cell production. Subsequently, solar cells were fabricated with either several or all layers comprising recycled materials. Every combination yielded efficiency comparable to cells constructed exclusively with fresh materials, demonstrating the efficacy of the developed recycling process. Our mass and value analysis highlights ITO glass has the highest recycling priority and the need for circular utilization for by-product chemicals, especially cleaning agents. Techno-economic projections suggest that the proposed recycling procedure has the potential to afford substantial cost savings. In the lab, recycling could reduce material costs by up to 63.7%, in industrial manufacturing by up to 61.4%. A life cycle assessment reveals this recycling method can reduce environmental impacts.
CRIS-Team Scopus Importer:2024-06-07

Cradle to Cradle Recycling of Perovskite Solar Cells - Wu, Zhenni; Babayeva, Gülüsüm; Zhang, Jiyun; Sytnyk, Mykhailo; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
Cradle-to-cradle recycling plays an important role in resolving one of the major upcoming challenges for photovoltaics in the energy transition-resource management. As photovoltaic production continues to grow, it absorbs a vast amount of resources. Cradle-to-cradle recycling is essential to keep these resources available perpetually and minimize waste generation. To achieve this, a new design paradigm for solar panels that puts recycling in its center is needed. In this study, we show first results of a perovskite solar cell that was created using such a design paradigm. We created a device with 18.1% efficiency and an architecture that facilitates disassembly of the functional layers. We show that the absorber material, MaPbI3 was used for the test device, can be recycled without causing a loss of solar cell efficiency.
CRIS-Team Scopus Importer:2024-12-16

DC sputter deposited TiO2 layers on FTO: towards a maximum photoelectrochemical response of photoanodes - Kim, Hyesung; Wang, Yue; Denisov, Nikita; Wu, Zhenni; Kment, Stepan; Schmuki, Patrik (Journal of Materials Science, 2022)
Abstract: In this work, we examine the photoelectrochemical response of TiO2 layers prepared by reactive DC sputter deposition on conductive glass (FTO). We show that adequate conditioning of the FTO by a very thin (few nm thick) Ti interlayer and optimizing the sputter parameters, compact TiO2 anatase layers can be produced that reach incident photocurrent conversion efficiencies (IPCE) maxima peaking at 75%. This is outperforming many of the best titania photoanode structures (including high surface area 1D and 3D titania structures). The key role of the interlayer is to promote the crystallization of titania in the anatase form during the annealing process (as opposed to rutile in the interlayer-free case). Without this interlayer, an IPCE maxima of ≈43% is obtained for otherwise identically processed electrodes. The present work thus describes a most simple straightforward approach for fabricating compact, high-efficiency TiO2 (anatase) photoanodes. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-15

Fluorine Aided Stabilization of Pt Single Atoms on TiO2Nanosheets and Strongly Enhanced Photocatalytic H2Evolution - Wu, Siming; Hwang, Imgon; Osuagwu, Benedict; Will, Johannes; Wu, Zhenni; Sarma, Bidyut Bikash; Pu, Fu Fei; Wang, Li Ying; Badura, Zdenek; Zoppellaro, Giorgio; Spiecker, Erdmann; Schmuki, Patrik (ACS Catalysis, 2022)
Trapping sites in single atom (SA) catalysts are critical to the stabilization and reactivity of isolated atoms. Herein, we show that anchoring of Pt SAs on TiO2 nanosheets is strongly aided by lattice incorporated fluorine species. Tailoring the speciation of fluorine on TiO2 nanosheets is a key factor for uniform and stable dispersion of the Pt SAs and high efficiency in Pt SA co-catalyzed photocatalytic H2 production. Fluorine-stabilized uniformly dispersed Pt SAs on the (001) surface of TiO2 can provide a remarkable photocatalytic activity (a H2 production rate of 45.3 mmol h-1 mg-1 Pt for 65 mW/cm2 365 nm light). This high (maximized) efficiency can be achieved with a remarkably low loading amount of Pt SAs on TiO2 nanosheets (0.03 wt %), which is far superior to Pt nanoparticles on a TiO2 nanosheet with the same or a higher loading amount. F-stabilized Pt SAs on TiO2 nanosheets also exhibit an excellent stability in long-term photocatalytic reactions.
CRIS-Team Scopus Importer:2022-12-23
Keywords: dark deposition; photocatalysis; single atom platinum; surface fluorination; titanium dioxide

Fluorine Aided Stabilization of Pt Single Atoms on TiO2 Nanosheets and Strongly Enhanced Photocatalytic H2 Evolution - Wu, Si-Ming; Hwang, Imgon; Osuagwu, Benedict; Will, Johannes; Wu, Zhenni; Sarma, Bidyut Bikash; Pu, Fu-Fei; Wang, Li-Ying; Badura, Zdeněk; Zoppellaro, Giorgio; Spiecker, Erdmann; Schmuki, Patrik (ACS Catalysis, 2022)
Trapping sites in single atom (SA) catalysts are critical to the stabilization and reactivity of isolated atoms. Herein, we show that anchoring of Pt SAs on TiO2 nanosheets is strongly aided by lattice incorporated fluorine species. Tailoring the speciation of fluorine on TiO2 nanosheets is a key factor for uniform and stable dispersion of the Pt SAs and high efficiency in Pt SA co-catalyzed photocatalytic H2 production. Fluorine-stabilized uniformly dispersed Pt SAs on the (001) surface of TiO2 can provide a remarkable photocatalytic activity (a H2 production rate of 45.3 mmol h–1 mg–1 Pt for 65 mW/cm2 365 nm light). This high (maximized) efficiency can be achieved with a remarkably low loading amount of Pt SAs on TiO2 nanosheets (0.03 wt %), which is far superior to Pt nanoparticles on a TiO2 nanosheet with the same or a higher loading amount. F-stabilized Pt SAs on TiO2 nanosheets also exhibit an excellent stability in long-term photocatalytic reactions.<br

Optimized Pt Single Atom Harvesting on TiO2 Nanotubes—Towards a Most Efficient Photocatalyst - Wu, Zhenni; Hwang, Imgon; Cha, Gi; Qin, Shanshan; Tomanec, Ondřej; Badura, Zdenek; Kment, Stepan; Zboril, Radek; Schmuki, Patrik (Small, 2021)
In the present work the authors show that anodic TiO2 nanotubes (NT) show excellent harvesting properties for Pt single atoms (Pt SAs) from highly dilute Pt solutions. The tube walls of anodic nanotubes, after adequate annealing to anatase, provide ample of suitable trapping sites—that is, surface Ti3+-Ov (Ov: oxygen vacancy) defects that are highly effective to extract and accumulate Pt in the form of SAs. A saturated (maximized) SA density can be achieved by an overnight immersion of a TiO2 NT layer to a H2PtCl6 solution with a concentration that is as low as 0.01 mm Pt. Such TiO2 NTs with surface trapped Pt SAs provide a maximized high activity for photocatalytic H2 generation (reaching a turnover frequency (TOF) of 1.24 × 106 h−1 at a density of 1.4 × 105 Pt atoms µm−2)—a higher loading with Pt nanoparticles does not further increase the photocatalytic activity. Overall, these findings show that anodic TiO2 nanotubes provide a remarkable substrate for Pt extraction and recovery from very dilute solutions that directly results in a highly efficient photocatalyst, fabricated by a simple immersion technique.
CRIS-Team Scopus Importer:2021-11-12
Keywords: dark deposition; hydrogen generation; photocatalysis; single-atom catalysis; TiO

Optimizing Perovskite Thin-Film Parameter Spaces with Machine Learning-Guided Robotic Platform for High-Performance Perovskite Solar Cells - Zhang, Jiyun; Liu, Bowen; Liu, Ziyi; Wu, Jianchang; Arnold, Simon; Shi, Hongyang; Osterrieder, Tobias; Hauch, Jens; Wu, Zhenni; Luo, Junsheng; Wagner, Jerrit; Berger, Christian; et al. (Advanced Energy Materials, 2023)
Simultaneously optimizing the processing parameters of functional thin films remains a challenge. The design and utilization of a fully automated platform called SPINBOT is presented for the engineering of solution-processed functional thin films. The SPINBOT is capable of performing experiments with high sampling variability through the unsupervised processing of hundreds of substrates with exceptional experimental control. Through the iterative optimization process enabled by the Bayesian optimization (BO) algorithm, the SPINBOT explores an intricate parameter space, continuously improving the quality and reproducibility of the produced thin films. This machine learning (ML)-guided reliable SPINBOT platform enables the acceleration of the optimization process of perovskite solar cells via a simple photoluminescence characterization of films. As a result, this study arrives at an optimal film that, when processed into a solar cell in an ambient atmosphere, immediately yields a champion power conversion efficiency (PCE) of 21.6% with satisfactory performance reproducibility. The unsealed devices retain 90% of their initial efficiency after 1100 h of continuous operation at 60–65 °C under metal-halide lamps. It is anticipated that the integration of robotic platforms with the intelligent algorithm will facilitate the widespread adoption of effective autonomous experimentation to address the evolving needs and constraints within the materials science research community.
CRIS-Team Scopus Importer:2023-11-10
Keywords: closed-loop optimization; efficient and stable devices; machine learning; manufacturing optimization; perovskite thin films; PL characterization; robotic platform

Photocatalytic Hydrogen Generation from Water-Annealed TiO2 Nanotubes with White and Grey Modification - Fu, Fan; Cha, Gi; Wu, Zhenni; Qin, Shanshan; Zhang, Yan; Chen, Yuyue; Schmuki, Patrik (ChemElectroChem, 2021)
In recent years, photocatalytic reactions on anodic TiO2 nanotubes have been intensively investigated. In order to show photocatalytic activity, anodically formed nanotubes need to be crystallized to anatase. This is conventionally done by thermal annealing in air at temperatures 400–600 °C. Recently, a so-called “water annealing” treatment has been reported to be effective to also create a highly active form for photocatalysis. Here we report on the feasibility of using a water annealing treatment of TiO2 nanotubes to create a photocatalyst for H2 production that is as active as conventional thermal annealing. If the water-annealed samples are additionally hydrogenated to a so-called “grey” modification, a further significant improvement of the photocatalytic activity for H2 evolution can be achieved – this without the use of any noble metal co-catalyst. A combination of water annealing, thermal annealing, followed by hydrogenation can deliver a H2 generation activity that is more than five times higher than that achieved by thermal annealing of anodic TiO2 nanotubes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: hydrogenation; optimized water annealing; TiO; titanium (III); water splitting

Revealing the Crystallization and Thermal-Induced Phase Evolution in Aromatic-Based Quasi-2D Perovskites Using a Robot-Based Platform - Zhang, Jiyun; Wu, Jianchang; Zhao, Yicheng; Zou, Yuqin; Barabash, Anastasia; Wu, Zhenni; Zhang, Kaicheng; Deng, Can; Elia, Jack; Li, Chaohui; Rocha Ortiz, Juan Sebastian; Liu, Chao; et al. (ACS Energy Letters, 2023)
Introducing large organic cations to form reduced-dimensional (quasi-2D) perovskites has proven to be effective in stabilizing three-dimensional perovskites. In this study, we synthesized 28 Ruddlesden-Popper-type quasi-2D perovskites using four aromatic-based cations (phenylmethylammonium (PMA), phenethylammonium (PEA), phenylpropylammonium (PPA), and phenylbutanammonium (PBA)) and systematically investigated their optoelectronic and structural properties and thermal stability. A counterintuitive finding that longer-chain PPA-based films exhibited relatively poorer stability compared to films with shorter-chain cations has been found. This instability in PPA-based samples is attributed to significant lattice distortion and a mismatched phase between face-sharing trimers, causing intense configurational strain. On the other hand, PBA-containing films maintained robust structural stability due to distinctive crystallization kinetics and a gradual phase-transformation process (from larger-n to lower-n phases) induced by a stronger steric-hindrance effect. Our study sheds light on the complex impact of aromatic-based cations on optoelectronic properties and stability of perovskites, providing guidelines for the rational compositional design engineering of highly stable perovskite material

Self-assembled monolayers enhance the efficiency of Pt single atom co-catalysts in photocatalytic H-2 generation - Wang, Yue; Hwang, Imgon; Wu, Zhenni; Schmuki, Patrik (Electrochemistry Communications, 2021)
Single atom (SA) catalysis, over the last 10 years, has become a forefront in heterogeneous catalysis, electrocatalysis, and most recently also in photocatalysis. Pt SAs on titania have been reported to be a highly effective co-catalyst in photocatalytic H-2 generation. Most recently, for the synthesis of SA loading on titania surfaces, some simple immersion techniques have been described. Here we introduce a so far unexplored but evidently very effective approach to enhance the effectivity of Pt SA co-catalysts on anodic TiO2 layers. For this, we first decorate TiO2 surfaces with a partial coverage of headgroups of silane self-assembled monolayers (SAMs) and then deposit Pt SAs on this SAM modified surface. We observe a significantly enhanced photocatalytic activity for H-2 generation using this sensitization of the surface with a modified SAM.
CRIS-Team WoS Importer:2022-05-20

Self-assembly and activation of a titania-nanotube based photocatalyst for H-2 evolution - Fu, Fan; Wu, Zhenni; Cha, Gi; Schmuki, Patrik (Chemical Communications, 2021)
Constructing an efficient photocatalyst for H-2 production generally requires the integration of several functional features in and on a semiconductor platform. This is conventionally done by a classic step-by-step synthesis. Here, we report the self-assembly of an amorphous titania nanotube based system when illuminated for extended time in suitable aqueous solutions. Over time, not only photodeposition of a co-catalyst can take place, but also in situ crystallization and morphology changes occur that can provide a higher H-2 production than observed for a classically assembled photocatalyst.
CRIS-Team WoS Importer:2021-07-09